2022
DOI: 10.3390/ijms23094922
|View full text |Cite
|
Sign up to set email alerts
|

CD44+ and CD133+ Non-Small Cell Lung Cancer Cells Exhibit DNA Damage Response Pathways and Dormant Polyploid Giant Cancer Cell Enrichment Relating to Their p53 Status

Abstract: Cancer stem cells (CSCs) play a critical role in the initiation, progression and therapy relapse of many cancers including non-small cell lung cancer (NSCLC). Here, we aimed to address the question of whether the FACS-sorted CSC-like (CD44+ &CD133+) vs. non-CSC (CD44−/CD133− isogenic subpopulations of p53wt A549 and p53null H1299 cells differ in terms of DNA-damage signaling and the appearance of “dormant” features, including polyploidy, which are early markers (predictors) of their sensitivity to genotoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 80 publications
1
17
1
Order By: Relevance
“…In the present study, the degree of MGCC enrichment was highest in LN-229 cells, compared to the modest (but still significant) enrichment in U-87 and the marginal one in U-251 cells ( Figure 1 d–f), suggesting that transactivation is functional either in wild-type or mutated p53 and its driven pathway might be associated with MGCC formation efficacy. This observation brings more support to our preceding hypothesis that under genotoxic and nutrient stress, such as IR exposure and serum starvation, functional p53 may promote entering a safer, presumably “dormant” state to preserve solid tumor cells from death irrespectively of their stemness [ 92 ].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In the present study, the degree of MGCC enrichment was highest in LN-229 cells, compared to the modest (but still significant) enrichment in U-87 and the marginal one in U-251 cells ( Figure 1 d–f), suggesting that transactivation is functional either in wild-type or mutated p53 and its driven pathway might be associated with MGCC formation efficacy. This observation brings more support to our preceding hypothesis that under genotoxic and nutrient stress, such as IR exposure and serum starvation, functional p53 may promote entering a safer, presumably “dormant” state to preserve solid tumor cells from death irrespectively of their stemness [ 92 ].…”
Section: Discussionsupporting
confidence: 73%
“…In this regard, we did not investigate polyploidy and stemness acquisition in our present study. Notwithstanding, such an observed early stress-induced response correlates quite well with time of appearance of “dormancy-related” features, including polyploidy, in CSC-like (CD44+/CD133+) vs. non-CSC (CD44-/CD133-) isogenic subpopulations of A549 and H1299 non-small lung cancer cells (NSCLCs) as an early marker (predictor) of their behavior after the same type of genotoxic stress [ 92 ]. Moreover, the behavior and dynamics of each feature’s appearance in lymphoblast [ 12 , 91 ] and solid (NSCLCs or GBM studied by us) tumors are supposed to be different.…”
Section: Discussionmentioning
confidence: 99%
“…However, we could not detect an increased expression of the stemness transcription factors SOX2, NANOG, and POU5F1 in the CD44 + populations. This is in contrast to other authors, who found an increased expression in CD44 + NSCLC cells compared to CD44 − cells [17,37]. However, they did not grow their cells as tumorspheres, prior to sorting, and the expression of pluripotency factors was much higher than adherent cells since tumorsphere culture is an enrichment of CSCs [38].…”
Section: Discussioncontrasting
confidence: 70%
“…124,126,146 P53 drives cells into a safer and more favourable dormant state, enhancing the adaptability and survival of PGCCs to irradiation stress. 66,147 The CHK1, CHK2-pCDC25C-Ser216cyclin B1-CDK1 and AURKA-Polo-like kinase 1 (PLK1)-pCDC25C-Ser198-cyclin B1-CDK1 signalling pathways are participant of PGCCs formation. 25,126 ataxia telangiectasiamutated gene (ATM)/ataxia telangiectasia mutated and Rad3-related (ATR)-P53-p21 axis induces cell dormancy and cell cycle arrest.…”
Section: Pgccs Achieve Dormancy Through Endoreplicative Cell Cyclementioning
confidence: 99%